Enrichment of all dichlorobenzene isomers transforming anaerobic mixed cultures from sediments - Quynh Phuong, Ngo; Thi Theu, Ngo; Thi Van Thi, Tran; Hien Trang, Nguyen; Thi Viet, Nguyen; Huu Dong, Nguyen; Hoa Duan, Tran (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4636, 2017)
Isomers of dichlorobenzene have been widely used in many industries and cause a big concern for the environment. Dichlorobeznenes were bio-transferred by 02 anaerobic mixed cultures enriched from 05 sediments  obtained in Thua Thien Hue province’s canal. The fisrt mixed culture, named M1 transferred all of isomers of dichlorobenzene with the pathway of preferentially dechlorinating singly-flanked chlorine substituents to produce monochlorobenzene as the end product although the culutre was able to remove isolated chlorine substituents. Reversely, the second mixed culture, named M2 transferred dichlorobenzenes with the pathway of preferentially removing isolated chlorine substituents to produce monochlorobenzene and benzene as intermediate and end product, respectively, except M2 culture enriched with 1,2-dichlorobenzene (benzene wa found in M2.2 culture). The ablility of dechlorination of M1 and M2 culture remained stable in a completely synthetic medium over three transfers which abloshed the environmental unkownfactors in sediments afecting the growth and dechlorinating ability of active anaerobes in the sediments